PHBV cycle of life using waste as a starting point: from production to recyclability - García-Chumillas, Salvador; Guerrero-Murcia, Teresa; Nicolás-Liza, María; Monzó, Fuensanta; Simica, Alexandra; Simó-Cabrera, Lorena; Martínez-Espinosa, Rosa María (Frontiers in Materials, 2024)
Global concern about plastic pollution is forcing new policies and modifications of human consumption as well as promoting new research lines aiming at the replacement of non-degradable plastics with other polymers more environmentally friendly. Addressing food waste and promoting circular economy strategies, among other approaches, are crucial in reducing environmental impacts and fostering sustainability in several sectors like the agri-food industry. The European Union's Circular Economy Action Plan is a significant initiative in this direction. Biotechnological processes, especially the valorisation of agri-food waste to produce highly marketed biomolecules like poly(3hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) using microorganisms as cellular factories, offer promising avenues for achieving these goals. PHBV is a biodegradable polymer firstly characterised as an isolated biopolymer from bacterial biomass. This biopolymer shows interesting physicochemical properties making possible immense potential in various applications due to its biocompatibility and sustainability, thus revealing it as a good candidate to replace plastics produced by chemical synthesis from petroleum (which are highly recalcitrant and consequently pollutants). This review critically analyses the PHBV synthesis and end-of-life scenarios from their synthesis using chemical and biological pathways, through the forms of biotechnological operation and production, to the forms described until the moment of recycling. Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Inglés (Estados Unidos) Con formato: Italiano (Italia) Con formato: Inglés (Estados Unidos